Decentralization and Strengthening of Districts in Papua: Analysis in the Perspective of Constitutional Law - Bauw, Lily (PT. Riset Press International, 2025)
This study aims to analyze the weaknesses of district authority in implementing Papua Special Autonomy and its impact on the implementation of government and public services and examine the obstacles in implementing decentralization in Papua, especially related to the position and authority of the district. The research method used in this study is the normative legal research method using a statutory, conceptual, and comparative approach. The results of this study reveal that district authority in implementing the Papua Special Autonomy policy has a crucial role in bringing public services closer to the community and increasing the effectiveness of local government administration. Based on Law Number 2 of 2021 and its derivative regulations (PP Number 106 of 2021 and PP Number 107 of 2021), districts have a strategic role in development planning, regional financial management, and local wisdom-based governance. Meanwhile, the obstacles in implementing Special Autonomy at the district level in Papua reflect broader challenges in the decentralization system and regional governance. Based on an analysis of Law Number 2 of 2021, PP Number 106 of 2021, and PP Number 107 of 2021, the main obstacles faced in the implementation of Special Autonomy in the district include: limited capacity of district officials, less than optimal financial management, weak coordination between institutions, and low community participation in the governance process.